Study of Variations of Citation-based Parameters for Selected Indian Science Journals - Dutta, Bidyarthi (Journal of Information and Knowledge, 2024)
The ratio of the total number of citations to the total number of cited papers was predicted as a constant by Garfield. But, later he observed the changing nature of this constant over time. Scientometricians called it the ‘Garfield Ratio’ rather than the ‘Garfield Constant’. ‘Garfield Ratio’ is a well-known citation-based parameter that indicates the average citation per cited article. However, Garfield still pointed out that behind this ratio some deeper regularity may be found. In this paper, an analysis of this indicator, the Garfield Ratio (GR)Y is attempted for twelve prominent Indian science journals from 2009 to 2020. Two other formulae for Garfield Ratio are introduced here, i.e. Modified Garfield Ratio for the year ‘Y’ (GRM)Y and Time-Normalised Garfield Ratio for the year ‘Y’ (GRN)Y. The year-wise analysis of these two Garfield Ratios, i.e., (GRM)Y and (GRN)Y for the twelve journals over twelve years is also carried out. The temporal variations of (GR)Y, (GRM)Y and (GRN)Y are interpreted by seven statistical parameters, i.e. mean, median, standard deviation, range, coefficient of variation, skewness and kurtosis. The temporal variations of (GR)Y for twelve journals are viewed by regression analysis to find out the best-fit function.